Pelatihan Keselamatan Dalam Pembelajaran Penjasorkes di SD Negeri se Kecamatan Arangpucung Tahun 2020 - Ruman; Kusmiyati; Friska (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2021)
The implementation of Thematic KKN is intended to foster empathy and concern among the academic community of STKIP Darussalam Cilacap towards, (1) various real problems faced by society and (2) sustainable development which is needed to make the nation's life intelligent and realize social welfare. The results of evaluating the level of knowledge of trainees regarding first aid for sports injuries showed an increase in pre-test results with an average value of 7 and post-test results with an average value of 9.4. In addition, participants' first aid skills improved, as shown by the results of the assessment of first aid practices carried out by participants when carrying out sports injuries.